Uji Mekanisme Antagonis Rizobakteri Terhadap Sclerotium rolfsii Penyebab Rebah Semai pada Tanaman Kacang Tanah - Agustin, Dyah Ayu; Abadi, Abdul Latief; Aini, Luqman Qurata (Agropross : National Conference Proceedings of Agriculture, 2022)
Sclerotium rolfsii is an important disease in peanut plants. S. rolfsii causes yield losses 25-50%. This research aims was to determine the mechanism of antagonists rhizobacteria in inhibiting the growth of S. rolfsii and suppressing the occurrence of damping off disease in peanut plants. The research stage include selecting rhizobacteria isolates trhough antagonistic test against S. rolfsii, observing hyphae abnormalities, analysis hydrolytic enzyme production, molecular identification 16S rRNA rhizobacteria, and test for suppression of damping off disease in peanut plants. The results showed that of the 16 rhizobacteria isolates, there were 4 isolates that were effective in inhibited the growth of S. rolfsii. Rhizobacteria that are effective in inhibited S. rolfsii cause abnormalities on hyphae in the form of hyphae colling, bending, shrinking, and lysis. Four isolates of antagonistic rhizobacteria were produce hydrolytic enzymes such as cellulase, chitinase, and protease. A total of 2 selected rhizobacteria isolates were able to increase the height plants and as many as 3 selected rhizobacteria isolates were able to increase the number of leaves of peanut plants compared to controls. Based on the disease suppression test, 4 selected rhizobacteria isolates were able to suppress the incidence of damping off disease in peanut plants equivalent to fungicides. Based on the moleculer identification 16S rRNA isolates G19, K009, R27, and R54 consecutively were identified as Klebsiella pneumoniae, Pseudomonas aeruginosa, Pseudomonas aeruginosa, and Enterobacter asburiae.